Analisis Kesesuaian Evaluasi Pembelajaran dalam RPP SKI Materi Walisongo dengan Prinsip Asesmen Kurikulum Merdeka di MIS Azrina Medan - Izmi Lutfiah; Nurmawati Nurmawati; Soraya Zairina Asmadi; Wan Tasya Luthfiah Anwar (Lembaga Yasin AlSys, 2026)
This study aimed to analyze the alignment of learning evaluation in the Sejarah Kebudayaan Islam (Islamic Cultural History, SKI) lesson plans (RPP) on the Walisongo topic with the assessment principles of the Kurikulum Merdeka at MIS Azrina Medan. A descriptive qualitative approach was employed through interviews, document analysis of SKI lesson plans and teaching modules, and indirect observation, and the data obtained were analyzed qualitatively based on field findings and document review. The results indicate that learning evaluation in the SKI lesson plans has included formative and summative assessments that measure students’ knowledge, skills, and attitudes. In general, the assessment system implemented has oriented toward the principles of the Kurikulum Merdeka, which are authentic, continuous, and focused on student development. However, refinement is still required in the instruments for student self-reflection and the assessment rubrics so that learning evaluation becomes more holistic, objective, and aligned with the spirit of the Kurikulum Merdeka. These findings underscore the importance of strengthening the design of learning evaluation in SKI lesson plans to support the realization of comprehensive assessment practices and to promote the improvement of learning quality in madrasah ibtidaiyah.